Place Names Documentation as Community-Based Language Conservation - Mall’u Demoski, Francisca; Alden, McKinley (Études Inuit Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2024)
Bristol Bay Native Corporation’s (BBNC) Bristol Bay Native Place Names Project is a 20-year initiative dedicated to celebrating the Sugpiaq/Alutiiq, Dena’ina, and Yup’ik Native place names in the Bristol Bay region of Southwest Alaska. Through this project, BBNC is committed to honoring the land-centered knowledge and environment that has long defined Alaska Native cultures. As traditional place names are increasingly replaced by English equivalents, this project serves to revitalize cultural and linguistic knowledge that connects our communities to the land. The Bristol Bay Native Place Names Project highlights the contributions of Alaska Native cultural workers, educators, community members, and knowledge bearers. It documents approximately 1,500 place names across three Alaska Native languages in the Bristol Bay region. The online publication of these names has received a remarkable response from the community, with growing use of traditional place names in daily life, navigation, search-and-rescue operations, oral histories, and land-based language education in schools. Overall, this initiative represents a form of Indigenous language revitalization driven by Alaska Native people for the benefit of their home communities, ensuring the continued connection to cultural heritage and fostering future generations’ understanding of their ancestral lands.